MANAGEMENT OF EXTRACURRICULAR PROGRAMS IN ENHANCING STUDENTS' CREATIVITY IN ELEMENTARY SCHOOLS - Iqna Urva Mumtahanah; Pramesti Reza Ayu Priyantari; Desi Ratna Tirtawati; Choirun Nisa (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2025)
This study aims to analyze how extracurricular program management is implemented in enhancing students’ creativity in elementary schools. Creativity is an important aspect of the development of elementary school- aged children because it plays a role in fostering critical, innovative, and independent thinking skills. This research employs a descriptive qualitative approach with data collection techniques including observation, in- depth interviews with principals, extracurricular teachers, and students, as well as documentation studies. The findings indicate that effective management of extracurricular programs involves thorough planning, organization of human resources and facilities, implementation of varied activities based on students’ interests, and regular evaluations that encourage continuous program improvement. Extracurricular activities such as arts, sports, and science provide opportunities for students to express their creative ideas and build self- confidence. Challenges encountered include limited facilities, restricted time, and insufficient training for instructors. However, with support from schools and parental involvement, extracurricular programs can serve as an effective platform for developing students’ creativity. The conclusion of this study is that structured extracurricular program management, oriented toward the development of students’ potential, can make a significant contribution to enhancing creativity at the elementary school level.